Fabrication and Magnetic Actuation of 3D‐Microprinted Multifunctional Hybrid Microstructures. Issue 10 (23rd August 2020) - Vieille, Victor; Pétrot, Roxane; Stéphan, Olivier; Delattre, Guillaume; Marchi, Florence; Verdier, Marc; Cugat, Orphée; Devillers, Thibaut
Abstract: Only achievable with two photons' polymerization, 3D printing at the micrometer scale is essential for the fabrication of complex objects such as photonic components, deformable microstructures, or microscaffolds for biological cells. Integrating magnetic materials inside those structures has made their remote actuation with an external magnetic field possible. However, the nature of the magnetic material, its volume, and precise position in the structure are keys for the efficiency, dexterity, and compatibility with optical or biological functions. Herein, an original approach consisting in the bonding of discrete and fully magnetic microbeads to unaffected 3D‐microprinted structures is presented. Implemented in combination with the fine control of optical and mechanical properties allowed by the careful design of the 3D architecture, it is applied to the fabrication of the first remotely tunable biconvex microlens (focal length of 18 µm). Combined with the additional precise positioning and magnetic orientation of multiple microbeads, the presented technique enables the fabrication of complex actuators such as a 100 µm microtweezer that can be translated, rotated, and opened with a single variable external magnetic field. The dexterity of this untethered micromanipulator is demonstrated through a pick‐and‐place operation of 40 µm objects in a confined environment. Abstract : A novel fabrication technique based on 3D printing with two‐photon polymerization and discrete bulk magnetic microbeads is presented. This new approach combined with the precise localization and orientation of magnetic moments inside the 3D‐printed structure allows for the elaboration of hybrid and multifunctional microactuators. Magnetically actuated microlens and dexterous 3D microgripper are demonstrated for the first time.